PENERAPAN FATWA DSN-MUI TENTANG MURABAHAH DI BANK SYARIAH - Hamli Syaifullah (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2018)
Fatwa DSN-MUI on Murabaha in Bank Syariah is very important to be applied, so that products that have murabahah akad can be confirmed in accordance with sharia principles. Shariah compliantness of all Sharia Bank's products become the main keywords, whether the Sharia Bank has actually run the business in accordance with the principles of sharia. In implementing the DSN-MUI Fatwa on Murabaha, it can be done through two ways, namely: SOP development and supervision conducted by the Sharia Supervisory Board (DPS). If the two things can be executed, then the Sharia Bank will be able to apply the Fatwa DSN-MUI in Bank Syariah about murabahah.